FAMILY COMMUNICATION IN THE ‘OLD’ FILM (2021): INTERPERSONAL PERSPECTIVE - Putra, Bakti Abdillah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Film is a medium that delivers social phenomenon that happens in the middle of society and certain messages for a problem. In a film, every character has different personality, especially when it comes to family. ‘Old’ (2021) tells a story in which a family spend their quality time at a holiday resort to create bonding moments. One day, they were invited to a secret beach and it turned out they grew older very quickly. That was when the conflict started and the integrity of a family was being challenged. This paper will discuss how communication within a family is analyzed from the view of interpersonal communication which is affected by conflict and social dynamic. The author will apply qualitative approach with content analysis method. From every scene that taken on this paper, the author will deliver the result of analysis into five components, such as openness, empathy, support, positive feeling, and commonality. The result shows that, from all five components, family communication addressed by the members takes them to unity and care, not something that can break them or conflicts